2010
DOI: 10.3892/ijo_00000680
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts associated with cancer cells keep enhanced migration activity after separation from cancer cells: A novel character of tumor educated fibroblasts

Abstract: Abstract.It is now clear that the association between cancer cells and recruited fibroblasts (cancer-associated fibroblasts; CAFs) leads to alteration of the biological properties of both types of cells and creates a specific microenvironment. Here we report a novel biological property of CAFs and its cellular mechanism using in vivo and in vitro model. Cultured CAFs derived from human lung cancer tissue displayed significantly higher migration activity in response to PDGF-BB than that of fibroblasts from corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…For instance, CAF-derived TGFb, EGF, FGFs, VEGF, MMPs, and a number of other factors have been implicated in epithelial cancer progression [Bhowmick et al, 2004b;Kalluri and Zeisberg, 2006;Ao et al, 2007]. Recently, Ishii et al [2010] reported that CAFs derived from human lung cancer specimens retain their enhanced migratory activity for a while after separation from the cancer cells. Thus, CAFs can maintain their ability to stimulate cancer progression suggesting that inhibition of generation of CAFs in tumor tissues could be a new target for control of primary cancer progression.…”
Section: Effects Of Growth Factors Neurotransmitter and Sex Steroidmentioning
confidence: 99%
“…For instance, CAF-derived TGFb, EGF, FGFs, VEGF, MMPs, and a number of other factors have been implicated in epithelial cancer progression [Bhowmick et al, 2004b;Kalluri and Zeisberg, 2006;Ao et al, 2007]. Recently, Ishii et al [2010] reported that CAFs derived from human lung cancer specimens retain their enhanced migratory activity for a while after separation from the cancer cells. Thus, CAFs can maintain their ability to stimulate cancer progression suggesting that inhibition of generation of CAFs in tumor tissues could be a new target for control of primary cancer progression.…”
Section: Effects Of Growth Factors Neurotransmitter and Sex Steroidmentioning
confidence: 99%
“…CAFs were prepared from human lung cancer tissue, as previously reported (33,34). The characteristics of the adenocarcinoma cases from which primary CAFs were obtained are shown in Supplementary Table S1.…”
Section: Fibroblast Culturementioning
confidence: 99%
“…After the cells were collected, CAFs were labeled with a phycoerythrin-labeled antifibroblast activation protein alpha (FAP-α) antibody for 30 min at 4°C in the dark. Fluorescent cells were identified as FAP-α-labeled CAFs, and non-fluorescent cells were identified as cancer cells [31], and then cultured for further expression analysis. For the studies involving inhibition or enhancement of glycolysis, CAFs were exposed to 2-deoxy-d-glucose (2-DG, 25 mmol/L) or fructose-1, 6-bisphosphate (FBP, 125 mmol/L) for 24 h before co-cultured with NSCLC cells.…”
Section: Patientsmentioning
confidence: 99%